2013
DOI: 10.1038/ismej.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

The species-rich assemblages of tintinnids (marine planktonic protists) are structured by mouth size

Abstract: Many microbial taxa in the marine plankton appear super-saturated in species richness. Here, we provide a partial explanation by analyzing how species are organized, species packing, in terms of both taxonomy and morphology. We focused on a well-studied group, tintinnid ciliates of the microzooplankton, in which feeding ecology is closely linked to morphology. Populations in three distinct systems were examined: an Eastern Mediterranean Gyre, a Western Mediterranean Gyre and the California Current. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…The morphospecies associations in each sample group differed in the size of the lorica aperture (that is, oral diameter), considering either the CMD or all samples ( Figure 6). Given that lorica oral diameter and prey size are correlated and tintinnids can consume prey as large as about half of their oral diameter (Dolan, 2010;Dolan et al, 2013b), the species that dominated inshore and offshore would consume mainly microplankton and nanoplankton, respectively ( Figure 6). Thus, competitive exclusion by dominant species could be linked to the changes in phytoplankton size fraction ratios estimated in the CMD and expected across the shelf as vertical mixing decreases (Figure 1d, Supplementary Figure S2A).…”
Section: Ecological Processes Linked To Spatial Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphospecies associations in each sample group differed in the size of the lorica aperture (that is, oral diameter), considering either the CMD or all samples ( Figure 6). Given that lorica oral diameter and prey size are correlated and tintinnids can consume prey as large as about half of their oral diameter (Dolan, 2010;Dolan et al, 2013b), the species that dominated inshore and offshore would consume mainly microplankton and nanoplankton, respectively ( Figure 6). Thus, competitive exclusion by dominant species could be linked to the changes in phytoplankton size fraction ratios estimated in the CMD and expected across the shelf as vertical mixing decreases (Figure 1d, Supplementary Figure S2A).…”
Section: Ecological Processes Linked To Spatial Patternsmentioning
confidence: 99%
“…Indeed, assemblages of tintinnid morphospecies differ markedly in the bathymetric, latitudinal and vertical profiles (for example, Alder, 1999;Modigh et al, 2003;Santoferrara and Alder, 2012), as well as in the seasonal cycle of temperate coasts (for example, Bojanić et al, 2012). Structuring of morphospecies assemblages has been explained by environmental selection in a coastal site (Sitran et al, 2009) or random dispersal in open waters (Dolan et al, 2007(Dolan et al, , 2009(Dolan et al, , 2013b, but the processes that affect assembly in the transitions between environments are unknown. Likewise, it is not known whether patterns and processes based on morphologies and molecules agree, as few distribution studies have used DNA sequences to target tintinnids and aloricate sister lineages (Doherty et al, 2010;Tamura et al, 2011;Bachy et al, 2014;Grattepanche et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using mouth size as a parameter to group tintinnid ciliates, Dolan et al (2013) showed that morphospecies distribution is related to the distribution of prey size in 2 Medi terranean gyres and in the California Current. Morphospecies richness in tintinnids has also been shown to correlate with phytoplankton concentration (Santoferrara & Alder 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While we have observed aloricate ciliates grazing on diatoms in images from the IFCB (not shown), this is not a common occurrence. Due to the close relationship between ciliate size and prey size (Kivi & Setala, 1995;Jonsson, 1987;Rassoulzadegan et al, 1988;Dolan et al, 2013), we can assume many ciliates at MVCO may be feeding on nanoplankton. Although the abundance of the <10 µm phytoplankton were low, ciliates may have responded quickly to their slight increases.…”
Section: Herbivorous Ciliate Structurementioning
confidence: 99%